Mechanized instrumentation of root canals: a literature review (Research, Society and Development, 2023)
Endodontics has been undergoing technological advances and clinical improvements, with increasingly faster and more effective treatments. The mechanized technique in root canal preparations reduced operative errors, increasing the clinical success of endodontic treatment. The objective of this work is to carry out a literature review in databases such as Scielo, BVS, Google Scholar, PubMed and some books, in the period between 2012 and 2022, on mechanized instrumentation in endodontic treatment, as well as to discuss its advantages and disadvantages in Endodontics. Based on the findings of this review, the importance of mechanized instruments for Endodontics is observed, both in the dentist's daily life and in promoting improvements in the quality and predictability of root canal preparation, in contrast to conventional ones. However, further studies are needed, as each instrument has its indications and limitations.